M1 cholinergic signaling in the brain modulates cytokine levels and splenic cell sub-phenotypes following cecal ligation and puncture - Mabel N. Abraham; Ana Nedeljkovic-Kurepa; Tiago D. Fernandes; Omar Yaipen; Mariana R. Brewer; Daniel E. Leisman; Matthew D. Taylor; Clifford S. Deutschman (BMC, 2024)
Abstract Background The contribution of the central nervous system to sepsis pathobiology is incompletely understood. In previous studies, administration of endotoxin to mice decreased activity of the vagus anti-inflammatory reflex. Treatment with the centrally-acting M1 muscarinic acetylcholine (ACh) receptor (M1AChR) attenuated this endotoxin-mediated change. We hypothesize that decreased M1AChR-mediated activity contributes to inflammation following cecal ligation and puncture (CLP), a mouse model of sepsis. Methods In male C57Bl/6 mice, we quantified basal forebrain cholinergic activity (immunostaining), hippocampal neuronal activity, serum cytokine/chemokine levels (ELISA) and splenic cell subtypes (flow cytometry) at baseline, following CLP and following CLP in mice also treated with the M1AChR agonist xanomeline. Results At 48 h. post-CLP, activity in basal forebrain cells expressing choline acetyltransferase (ChAT) was half of that observed at baseline. Lower activity was also noted in the hippocampus, which contains projections from ChAT-expressing basal forebrain neurons. Serum levels of TNFα, IL-1β, MIP-1α, IL-6, KC and G-CSF were higher post-CLP than at baseline. Post-CLP numbers of splenic macrophages and inflammatory monocytes, TNFα+ and ILβ+ neutrophils and ILβ+ monocytes were higher than baseline while numbers of central Dendritic Cells (cDCs), CD4+ and CD8+ T cells were lower. When, following CLP, mice were treated with xanomeline activity in basal forebrain ChAT-expressing neurons and in the hippocampus was significantly higher than in untreated animals. Post-CLP serum concentrations of TNFα, IL-1β, and MIP-1α, but not of IL-6, KC and G-CSF, were significantly lower in xanomeline-treated mice than in untreated mice. Post-CLP numbers of splenic neutrophils, macrophages, inflammatory monocytes and TNFα+ neutrophils also were lower in xanomeline-treated mice than in untreated animals. Percentages of IL-1β+ neutrophils, IL-1β+ monocytes, cDCs, CD4 + T cells and CD8 + T cells were similar in xanomeline-treated and untreated post-CLP mice. Conclusion Our findings indicate that M1AChR-mediated responses modulate CLP-induced alterations in serum levels of some, but not all, cytokines/chemokines and affected splenic immune response phenotypes.